For an ethics of otherness in pandemic times (PerCursos, 2021)
This essay addresses the SARS-Cov-2 pandemic, which caused Covid-19, and the contradictory thinking regarding the social isolation measures adopted by state governments in Brazil in the light of Emmanuel Levinas' philosophy. In this sense, the work aims to bring another look at this crisis, highlighting the ethics of otherness as the first philosophy for facing this health crisis. In the episode analyzed, it was observed that the search for self-interests does not consider those of the other, not paying attention to care related to their physical and mental integrity. The economic argument appears as a central element for breaking horizontal isolation overlapping lives. The normalization of deaths as a result of risk analysis that does not consider the human condition, producing the false impression that a vertical isolation would be sufficient to manage the crisis. In this sense, we emphasize the need for a perception of the world based on an ethics of otherness that highlights and emphasizes the responsibility of the same with the other and, mainly, the necessary preservation of life as a priority, above any possible interests.
Keywords: pandemic; ethics of otherness; philosophy